Clinical Outcomes of Molecular Tumor Boards: A Systematic Review. (2021) - Larson, Kara L.; Huang, Bin; Weiss, Heidi L.; Hull, Pam; Westgate, Philip M.; Miller, Rachel W.; Arnold, Susanne M.; Kolesar, Jill M.
Abstract : PURPOSE: We conducted this systematic review to evaluate the clinical outcomes associated with molecular tumor board (MTB) review in patients with cancer. METHODS: A systematic search of PubMed was performed to identify studies reporting clinical outcomes in patients with cancer who were reviewed by an MTB. To be included, studies had to report clinical outcomes, including clinical benefit, response, progression-free survival, or overall survival. Two reviewers independently selected studies and assessed quality with the Quality Assessment Tool for Before-After (Pre-Post) Studies with No Control Group or the Quality Assessment Tool for Observational Cohort and Cross-Sectional Studies depending on the type of study being reviewed. RESULTS: Fourteen studies were included with a total of 3, 328 patients with cancer. All studies included patients without standard-of-care treatment options and usually with multiple prior lines of therapy. In studies reporting response rates, patients receiving MTB-recommended therapy had overall response rates ranging from 0% to 67%. In the only trial powered on clinical outcome and including a control group, the group receiving MTB-recommended therapy had significantly improved rate of progression-free survival compared with those receiving conventional therapy. CONCLUSION: Although data quality is limited by a lack of prospective randomized controlled trials, MTBs appear to improve clinical outcomes for patients with cancer. Future research should concentrate on prospective trials and standardization of approach and outcomes.